The Relationship Between the Level of Knowledge, Attitude, and Behavior of Pregnant Women on Compliance with Iron Tablet (Ferrous Sulfate) Consumption and the Incidence of Anemia During Pregnancy - Fadillah; Athalia Rizqi; Amalia Resy (Sriwijaya Journal of Medicine, 2024)
Anemia is a direct or indirect cause of maternal mortality. Anemia is associated with maternal morbidity rates. The government’s effort to address anemia is to provide iron supplements (Ferrous Sulfate). The success of iron supplement administration depends on whether or not pregnant women take iron tablets. This study aims to determine the relationship between the level of knowledge, attitude, and behavior of pregnant women on compliance with iron tablet (Ferrous Sulfate) consumption and the incidence of anemia during pregnancy. This observational analytic study used a cross-sectional design with primary data from pregnant women at Puskesmas Pembina Palembang. 100 samples that met the inclusion and exclusion criteria were selected through consecutive sampling techniques. Statistical analysis results showed that 80% of respondents were not anemic while 20% were anemic. The respondents with a high level of knowledge mostly had positive attitudes (81%), positive behavior (94%), and compliance with iron tablet consumption during pregnancy (83%). The Chi-Square test and Fisher's Exact test showed a significant relationship between knowledge level (p-value = 0.000, OR = 11.746), attitude (p-value = 0.000, OR = 34.167), behavior (p-value = 0.001, OR = 7.309), and compliance with iron tablet consumption (p-value = 0.040, OR = 3.769) and the incidence of anemia during pregnancy. This study concludes that there is a relationship between the level of knowledge, attitude, and behavior of pregnant women on compliance with iron tablet (Ferrous Sulfate) consumption and the incidence of anemia during pregnancy.